School Stakeholder’s Support on the Use of Youth Information and Counseling Centers (PIK-R) - Isni, Khoiriyah; Matahari, Ratu (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
School stakeholder’s support greatly affects PIK-R utilization by students. The problem is that school stakeholders are often only responsible but do not play an active role in PIK-R implementation. The purpose of this study was to analyze the support of school stakeholders on the utilization of PIK-R Wijaya Kusuma SMAN 1 Srandakan. This research used qualitative research with case study approach. Key informants were principals, teachers PIK-R coach, guidance and counseling teachers, and peer counselors as triangulan. The data were collected through in-depth interviews. The results showed that the support of school stakeholders on the utilization of PIK-R wijaya kusuma was satisfactory. The support provided were in the form of active participation and involvement such as school counseling for students who experience problems, support in funding PIK-R activities, and cooperation efforts with other agencies. Some teachers were involved in health information socialization activities. Capacity building and skills related to adolescent health were also required by all teachers, so that all parties had the same understanding of PIK-R and gave full support to the utilization of PIK-R Wijaya Kusuma.